Bio-barrier-adaptable biomimetic nanomedicines combined with ultrasound for enhanced cancer therapy - Juan Guo; Xueting Pan; Qingyuan Wu; Ping Li; Chaohui Wang; Shuang Liu; Haoyuan Zhang; Zezhong Huang; Xiaozhou Mou; Huiyu Liu; Jiajia Xue (Signal Transduction and Targeted Therapy)
Abstract Addressing the critical biological barriers of targeted accumulation and deep tumor penetration remains essential for the clinical translation of nanomedicines. However, existing nanomedicines often face challenges during in vivo transportation, including immune clearance, tumor microenvironmental barriers, and limited vascular permeability, which collectively reduce drug delivery efficiency and compromise therapeutic efficacy. Here, we present a bio-barrier-adaptable biomimetic nanoplatform, MSF@CCM, which integrates a mesoporous silica-loaded iron oxyhydroxide (MSF) core camouflaged with a homologous membrane. This design conferred dual functionality: (1) enhanced tumor accumulation and immune evasion by exploiting homologous cell-cell interactions and mimicking “self” markers, thereby effectively bypassing macrophage clearance and surpassing the limitations of traditional targeted drug delivery; and (2) amplified ultrasound (US)-mediated intratumoral penetration. The MSF core, with its unique porous structure and rough surface, significantly enhanced US cavitation effects, transiently disrupting tumor vasculature and facilitating deep penetration of nanomedicines. Upon US triggering, MSF@CCM effectively disrupted intracellular redox homeostasis, potently inducing ferroptosis via lipid peroxidation accumulation, mitochondrial morphological changes, and decreased key protein expression. This combined therapeutic strategy achieved a remarkable 96.5% tumor growth inhibition in vivo while maintaining favorable biocompatibility. Our findings establish a novel paradigm for overcoming multidimensional bio-barriers through biohybrid engineering and physical energy synergy, offering a promising modality for enhanced cancer therapy.